The rice foot rot pathogen Dickeya zeae alters the in‐field plant microbiome. (25th August 2021) - Bez, Cristina; Esposito, Alfonso; Thuy, Hang Dinh; Nguyen Hong, Minh; Valè, Giampiero; Licastro, Danilo; Bertani, Iris; Piazza, Silvano; Venturi, Vittorio
Summary: Studies on bacterial plant diseases have thus far been focused on the single bacterial species causing the disease, with very little attention given to the many other microorganisms present in the microbiome. This study intends to use pathobiome analysis of the rice foot rot disease, caused by Dickeya zeae, as a case study to investigate the effects of this bacterial pathogen to the total resident microbiome and to highlight possible interactions between the pathogen and the members of the community involved in the disease process. The microbiome of asymptomatic and the pathobiome of foot‐rot symptomatic field‐grown rice plants over two growing periods and belonging to two rice cultivars were determined via 16S rRNA gene amplicon sequencing. Results showed that the presence of D. zeae is associated with an alteration of the resident bacterial community in terms of species composition, abundance and richness, leading to the formation of microbial consortia linked to the disease state. Several bacterial species were significantly co‐presented with the pathogen in the two growing periods suggesting that they could be involved in the disease process. Besides, culture‐dependent isolation and in planta inoculation studies of a bacterial member of the pathobiome, identified as positive correlated with the pathogen in our in silico analysis, indicated that it benefits from the presence of D. zeae . A similar microbiome/pathobiome experiment was also performed in a symptomatically different rice disease evidencing that not all plant diseases have the same consequence/relationship with the plant microbiome. This study moves away from a pathogen‐focused stance and goes towards a more ecological perception considering the effect of the entire microbial community which could be involved in the pathogenesis, persistence, transmission and evolution of plant pathogens.